A template method to measure the tt¯ polarisation - Aguilar-Saavedra, J.A. (2022)
We develop a template method for the measurement of the polarisation of t ¯t pairs produced in hadron collisions. The method would allow to extract the individual fractions of tL ¯tL , tR ¯tR, tL ¯tR and tR ¯tL pairs with a fit to data, where L, R refer to the polarisation along any axis. These polarisation fractions have not been independently measured at present. Secondarily, the method also provides the net polarisation of t and ¯t, aswell as their spin correlation for arbitrary axes.